(untitled) (Raparin Journal of Humanities (RJH), 2025)
The aftermath of World War II witnessed significant changes in China, marked by a civil war between the Chinese Communist Party, led by Mao Zedong, and the Chinese Nationalist Party (Kuomintang), led by Chiang Kai-shek. The conflict culminated in a victory for the Communists and the establishment of the People’s Republic of China in Beijing in 1949. Chiang Kai-shek and his followers retreated to Taiwan, where they declared the Republic of China with its capital in Taipei. Since then, Taiwan has claimed to be the legitimate government of all Chinese territory. Conversely, the People’s Republic of China has sought to reintegrate Taiwan under its "one country, two systems" framework, introduced by the Communist Party in the 1980s. Meanwhile, the United States has supported Taiwan and endeavored to safeguard its interests in the region. The study, entitled "The Taiwan issue in the context of the official positions of the People’s Republic of China and the United States of America", discusses the official positions of the parties concerned on the Taiwan issue. The importance of this study lies in Taiwan’s strategic location; any change in its current situation could threaten the regional balance. The study answers several important questions: Is the Taiwan issue a domestic matter, as claimed by China, or is it an international one? What are the official views of China and the United States on the Taiwan issue? To answer these questions, the study uses historical and descriptive-analytical methods based on library literature and is organized into five sections. These sections include a historical overview of the Taiwan issue, an examination of key mechanisms and strategies for resolving the conflict, and an exploration of the official positions and policies of Taiwan, the People’s Republic of China, and the United States regarding the Taiwan issue.